Provisions of Minimum Age of Marriage in Indonesia: Amendments Efforts and Responses - Kholifatun Nur Mustofa (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2018)
This paper examines the provisions of the minimum age of marriage by considering regulations in various Muslim countries. Besides, this paper also discusses why Indonesia experienced resistance in changing the rules of the minimum age. Using a sociological approach, this paper examines the minimum age limit in various Muslim countries and efforts in renewal the minimum age limit in Indonesia. Data collection is done through literature review, decisions, and related journals. This data is supported by the information from interviews on the judge’s attitude and response. The author interviewed 6 judges of the Bantul and Wonosari Religious Courts. This paper confirms that efforts made by several institutions to raise the minimum age of marriage have been made. One of them is the submission of Judicial Review No. 30-74 / PUU-XI / 2014 to the Constitutional Court, which was unfortunately rejected. One of the legal considerations of the Constitutional Court Judge is that the application is considered contrary to the 1945 Constitution. The prevailing customary law and cultural diversity in Indonesia have significant influence in increasing the minimum age, because one community has different views with others on the minimum boundary age of marriage. Besides, the Constitutional Court judges consider that raising the minimum age does not have a significant influence on reducing child marriages and some other adverse effects, but that influence emerges from the internet. The study also argues that these changes are considered not in harmony with all the different interests of society. This was also in line with the response of 6 judges in the Bantul and Wonosari Religious Courts.